INHIBITING PURCHASE INTENTIONS: THE IMPACT OF INAPPROPRIATE BRAND SPEECH ON SOCIAL MEDIA ON CONSUMER ENGAGEMENT BEHAVIOR - Budi Raharja, Arif; Ichwanudin, Wawan; Faisal, Ijang (Yayasan Kreatif Indonesia Emas, 2024)
In an increasingly connected digital era, social media has become the primary platform where brands and consumers interact directly. However, these interactions don't always go smoothly, especially when brands engage in inappropriate remarks on social media. This research aims to identify the impact of inappropriate brand remarks on social media on consumers' engagement behavior and their purchase intentions. Through literature analysis and discussion, it was found that consumers tend to respond negatively to brands that engage in inappropriate behavior on social media, which can result in a decrease in consumer trust, loyalty and engagement towards the brand. Additionally, this negative impact can also influence consumer purchase intentions, with consumers becoming hesitant to purchase products or services from brands that engage in inappropriate behavior. Effective communications strategies, including a focus on transparency, responsiveness and consumer education, can help brands reduce the risk of inappropriate speech and maintain or increase consumer engagement and trust in their brand. Therefore, it is important for brands to pay attention to how they interact with consumers on social media and ensure that every word they make reflects the brand's values and is sensitive to consumers' needs and desires.